Nanocrystalline Materials - Movahedi, Behrooz (IntechOpen, 2020)
The term "nanocrystalline materials" relates to the sizes of structural elements. The range of application of these materials is huge, such as more efficient catalysts, films, magnetic materials, protective coatings, and biological and biomaterials. Many compounds and elements, if made on the nanoscale, behave quite differently from how they would have in their conventional state. The overall purpose of this book, "Nanocrystalline Materials", is to provide present selected advanced topics on nanocrystals, allowing the book to be a good resource for scholars and students of material science, nanotechnology, and physical chemistry.